DAMPAK PEMBELAJARAN MENULIS BERBASIS WEBQUEST TERHADAP KETERAMPILAN MENULIS AKADEMIK DAN BERPIKIR KRITIS - Ana Widyastuti (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
The purpose of this study was to investigate the impact of WebQuest-based writing learning on academic writing skills and critical thinking skills. The method used in this study was a quasi-experimental method involving 250 high school students in grades 10–12. Participants were divided into two groups using random sampling techniques, namely the experimental group and the control group. The experimental group received WebQuest-based writing instruction, while the control group received face-to-face classes. The instruments used were a critical thinking measurement scale to measure critical thinking skills and an academic writing skills assessment form. Data analysis used MANOVA and MANCOVA tests. The results showed that WebQuest-based writing learning was more effective in improving academic writing skills and critical thinking skills compared to traditional face-to-face writing learning. The improvement in academic writing skills showed significant improvements in all aspects, namely task achievement, cohesion and coherence, lexical accuracy, and grammatical accuracy. This improvement occurred because the WebQuest-based learning structure pattern was able to hone higher-order thinking skills, which included the introduction stage, task components, process components, conclusions, and evaluation components. Several aspects of critical thinking skills that showed significant improvement were analysis, evaluation, and deductive reasoning. However, inference and inductive reasoning skills showed less significant improvement. This is due to the deductive-inductive nature of online teaching. Therefore, WebQuest-based writing learning can improve writing and critical thinking skills.